Focused Ultrasound-Enhanced Drug Delivery to Brain Tumors: Quantitative and Translational Insights from CNS Physiologically Based Pharmacokinetic Modeling - Andrew Wu; Charuka Wickramasinghe; Yuanyuan Jiang; Xun Bao; Jing Li (Clinical Cancer Research, 2026)
Abstract Purpose: Successful clinical translation of focused ultrasound (FUS)-induced blood-brain barrier (BBB) opening strategy to brain cancer therapy has been hindered by limited quantitative understanding of CNS pharmacokinetics. Using a physiologically based pharmacokinetic (PBPK) modeling framework, this study aimed to quantitatively characterize FUS-modulated CNS pharmacokinetics and identify key determinants of potential clinical benefits. Experimental Design: A previously validated 9-compartment CNS PBPK model framework was extended to incorporate FUS-induced BBB opening (with explicitly defined onset time, duration, and magnitude) in an infiltrative tumor compartment (T2), while infiltrative tumor (T1) presenting an intact BBB and tumor core (T3) presenting a continuous BBB disruption. The model was developed for four therapeutic agents, including the HER2 monoclonal antibody trastuzumab, antibody-drug conjugates (T-DM1 and T-DXd), and small-molecule temozolomide. Results: Model simulations indicate that FUS-modulated CNS pharmacokinetics are governed by the interplay between systemic pharmacokinetics and BBB transport kinetics. Concurrent BBB opening and drug administration maximizes tumor penetration across all four model drugs. Trastuzumab and antibody–drug conjugates benefit from larger and sustained BBB opening, whereas temozolomide requires precise temporal alignment of BBB opening with systemic exposure. Integration of CNS pharmacokinetics with pharmacological potency suggests that FUS-induced BBB opening is most likely to improve intracranial efficacy for T-DM1 and T-DXd, but not trastuzumab; for temozolomide, benefit may be restricted to patients with favorable tumor biology. Conclusions: These quantitative and translational insights offer a strategic framework for selecting therapeutic agents and refining FUS parameters to facilitate rational clinical development of FUS-induced BBB opening strategy in brain cancer therapy.